Experiences with perinatal death reviews in South Africa—the Perinatal Problem Identification Programme: scaling up from programme to province to country. (September 2014) - Rhoda, NR; Greenfield, D; Muller, M; Prinsloo, R; Pattinson, RC; Kauchali, S; Kerber, K
Abstract : The Perinatal Problem Identification Programme (PPIP) was designed and developed in South Africa as a facility audit tool for perinatal deaths. It has been used by only a few hospitals since the late 1990s, but since the country's commitment to achieve Millennium Development Goal 4—the use of PPIP is now mandatory for all facilities delivering pregnant mothers and caring for newborns. To date 588 sites, representing 73% of the deliveries captured by the District Health Information System for South Africa, provide data to the national database at the Medical Research Council Unit for Maternal and Infant Health Care Strategies in Pretoria.